Molecular Spring‐like Triple‐Helix Coordination Polymers as Dual‐Stress and Thermally Responsive Crystalline Metal–Organic Materials - Mei, Lei; An, Shu‐wen; Hu, Kong‐qiu; Wang, Lin; Yu, Ji‐pan; Huang, Zhi‐wei; Kong, Xiang‐he; Xia, Chuan‐qin; Chai, Zhi‐fang; Shi, Wei‐qun (Angewandte Chemie, 2020)
Elastic metal–organic materials (MOMs) capable of multiple stimuli‐responsiveness based on dual‐stress and thermally responsive triple‐helix coordination polymers are presented. The strong metal‐coordination linkage and the flexibility of organic linkers in these MOMs, rather than the 4 Å stacking interactions observed in organic crystals, causes the helical chain to act like a molecular spring and thus accounts for their macroscopic elasticity. The thermosalient effect of elastic MOMs is reported for the first time. Crystal structure analyses at different temperatures reveal that this thermoresponsiveness is achieved by adaptive regulation of the triple‐helix chains by fine‐tuning the opening angle of flexible V‐shaped organic linkers and rotation of its lateral conjugated groups to resist possible expansion, thus demonstrating the vital role of adaptive reorganization of triple‐helix metal–organic chains as a molecular spring‐like motif in crystal jumping. Dual‐stress and thermally responsive crystalline metal–organic materials (MOMs) based on molecular spring‐like triple‐helix coordination polymers are presented. As the first example of thermosalient effect in elastic MOMs, these compounds undergo elastic flexure upon external stress as well as cracking and jumping after thermal treatment.